PERAN IMC DALAM PEMILIHAN MOMMILK MANAHAN SOLO SEBAGAI PILIHAN KUNJUNGAN KONSUMEN - Endang Sri Purwaningsih; Dian Purworini (Universitas Muhammadiyah Surakarta, 2016)
This study is to explore the IMC activity conducted by Mommilk Manahan Solo in attracting consumen interest. The research was conducted in Mommilk restaurant, Surakarta city. The quantitative descriptive methodology arranged to support the study while the measurement scale used Likert scale. The sample of this study was Mommilk costumers. The questioners were distributed to gauge the IMC activity, which can be devided into three specific factors; promotion and direct sell, public relation, and advertisement. In the outline of factors are the variables that influence the customers in selecting Mommilk as a preference. The result shows that the IMC activity is positively influence costumers to choose Mommilk as a preference. This study finds that several actions taken by the restaurant management successfully influenced the customers to choose Mommilk instead of others restaurants. Those actions become refence for the management to develop the service in order to attract the costumers.